PPAR‐γ in innate and adaptive lung immunity. Issue 4 (16th May 2018) - Nobs, Samuel Philip; Kopf, Manfred
Abstract: The transcription factor PPAR‐γ (peroxisome proliferator‐activated receptor‐γ) is a key regulator of lung immunity exhibiting multiple cell type specific roles in controlling development and function of the lung immune system. It is strictly required for the generation of alveolar macrophages by controlling differentiation of fetal lung monocyte precursors. Furthermore, it plays an important role in lung allergic inflammation by licensing lung dendritic cell t helper 2 (Th2) priming capacity as well as acting as a master transcription factor for pathogenic Th2 cells. Due to this plethora of functions and its involvement in multiple pulmonary diseases including asthma and pulmonary alveolar proteinosis, understanding the role of PPAR‐γ in lung immunity is an important subject of ongoing research. Abstract : Review on novel role of PPAR‐γ in immunity.